Symbiotic Interaction Enhances the Recovery of Endangered Tree Species in the Fragmented Maulino Forest - Torres-Díaz, Cristian; Valladares, Moisés A.; Acuña-Rodríguez, Ian S.; Ballesteros, Gabriel I.; Barrera, Andrea; Atala, Cristian; Molina-Montenegro, Marco A. (Frontiers in Plant Science, 2021)
Beneficial plant-associated microorganisms, such as fungal endophytes, are key partners that normally improve plant survival under different environmental stresses. It has been shown that microorganisms from extreme environments, like those associated with the roots of Antarctica plants, can be good partners to increase the performance of crop plants and to restore endangered native plants. Nothofagus alessandrii and N. glauca, are among the most endangered species of Chile, restricted to a narrow and/or limited distributional range associated mainly to the Maulino forest in Chile. Here we evaluated the effect of the inoculation with a fungal consortium of root endophytes isolated from the Antarctic host plant Colobanthus quitensis on the ecophysiological performance (photosynthesis, water use efficiency and growth) of both endangered tree species. We also, tested how Antarctic root-fungal endophytes could affect the potential distribution of N. alessandrii through niche modeling. Additionally, we conducted a transplant experiment recording plant survival on two years in order to validate the model. Lastly, to evaluate if inoculation with Antarctic endophytes has negative impacts on native soil microorganisms, we compared the biodiversity of fungi and bacterial in the rhizospheric soil of transplanted individuals of N. alessandrii inoculated and non-inoculated with fungal endophytes. We found that inoculation with root-endophytes produced significant increases in N. alessandrii and N. glauca photosynthetic rates, water use efficiencies and cumulative growth. In N. alessandrii, seedling survival was significantly greater on inoculated plants compared with non-inoculated individuals. For this species, a spatial distribution modeling revealed that, inoculation with root-fungal endophytes could potentially increase the current distributional range by almost three-fold. Inoculation with root-fungal endophytes, did not affect native rhizospheric microbiome profiles, nor in terms of species abundance or diversity. Our results suggest that the studied consortium of Antarctic root-fungal endophytes improve the ecophysiological performance as well as the survival of inoculated trees and can be used as a biotechnological tool for the restoration of endangered tree species.